Efektywne zarządzanie programami sprzedażowymi na przykładzie rynku papierosów w Polsce - Majstrzyk, Tomasz (My University, 2011)
The topic of master thesis is: “Effective managemen t of sales programs in case of Polish cigarette market.”. Both in terms of continuous restriction of the cigarette market and the limitation of sales supporting tools, the topic is very common and significant nowadays. The most essential goal is to design an effective tool supporting sale of a particular product. What is more, there are pointed few analyses essential in the process of designing sales programs and the methods of both current control and final evaluation. In this case, there is presented a desk research which is based on literature studies and the analyses of secondary data. The main part of these thesis determines two marketing surveys: one that presents the behavior of points of sale in case of sales programs in B2B relations between the producer and point of sale, and second that confirms the validity of sales programs in B2C relations between consumer and point of sale. The primary research was conducted nationwide on 57 respondents. The technique of research was direct interview. The secondary research, which plays supporting roles, was conducted nationwide as well, but the technique was different – distributed questionnaire. The scale was completely different as well, because it was done by 5 546 respondents. These marketing researches was such a foundation to the presented solution of the sales program which are presented in the last chapter.

Tematem pracy magisterskiej jest: „Efektywne zarządzanie programami sprzedażowymi na przykładzie rynku papierosów w Polsce”. W pracy ograniczono się do relacji B2B, ze względu na bardzo duże różnice w specyfice programów sprzedażowych pomiędzy tymi kierowanymi bezpośrednio do punktu sprzedaży detalicznej, a do konsumenta. Głównym celem pracy magisterskiej jest analiza procesu efektywnego zarządzania programami sprzedażowymi na rynku papierosów w Polsce w relacjach B2B. Kluczowym elementem projektu są badania bezpośrednie. Mają one charakter ogólnopolski i zostały przeprowadzone na próbie 57 punktów sprzedaży, reprezentowanych zarówno przez ich właścicieli, jak również przez sprzedawców w nich zatrudnionych. Drugie badanie marketingowe przeprowadzone na potrzeby pracy miało charakter wspomagający, gdyż dotyczyło zachowań konsumentów podczas procesu zakupu papierosów. Badanie to było zrealizowane przy wykorzystaniu techniki ankiety rozdawanej, zostało przeprowadzone na próbie 5 546 konsumentów i miało charakter ogólnopolski. Pracę kończy podsumowanie zawierające kluczowe wnioski z badań.
Effective management of sales programs in case of Polish cigarette market
Keywords: rynek papierosów w Polsce; zarządzanie; efektywność; relacje B2B; program sprzedażowy; sales program; cigarette market in Poland; management; efficiency; B2B relations